2014
DOI: 10.1002/jcp.24689
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib/Regorafenib and Lapatinib Interact to kill CNS Tumor Cells

Abstract: The present studies were to determine whether the multi-kinase inhibitor sorafenib or its derivative regorafenib interacted with the ERBB1/ERBB2 inhibitor lapatinib to kill CNS tumor cells. In multiple CNS tumor cell types sorafenib and lapatinib interacted in a greater than additive fashion to cause tumor cell death. Tumor cells lacking PTEN, and anoikis or lapatinib resistant cells were as sensitive to the drug combination as cells expressing PTEN or parental cells, respectively. Similar data were obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The (−)‐cananodine (as a rupestine analog) is proven to be five times more potent as a cytotoxic agent than the standard drug “sorafenib,” against HepG2 and HepG2.2.15 cell lines with IC 50 0.94 and 16.0 μM, respectively (Shelton, ). Sorafenib/Regorafeand and Lapatinib are commercial drugs used for the treatment of breast cancer and other solid tumors (Hamed, Tavallai, Grant, Poklepovic, & Dent, ).…”
Section: The Chemistry and Pharmacology Of Artemisia Alkaloids/alliedmentioning
confidence: 99%
“…The (−)‐cananodine (as a rupestine analog) is proven to be five times more potent as a cytotoxic agent than the standard drug “sorafenib,” against HepG2 and HepG2.2.15 cell lines with IC 50 0.94 and 16.0 μM, respectively (Shelton, ). Sorafenib/Regorafeand and Lapatinib are commercial drugs used for the treatment of breast cancer and other solid tumors (Hamed, Tavallai, Grant, Poklepovic, & Dent, ).…”
Section: The Chemistry and Pharmacology Of Artemisia Alkaloids/alliedmentioning
confidence: 99%
“…These alterations required a revision of the response assessment in neuro-oncology (RANO) criteria to include non-enhancing T2/fluid attenuated inversion recovery (FLAIR) lesions as a new criterion for glioma progression [7]. Regorafenib (REG) is a multikinase inhibitor that inhibits, amongst others, the vascular endothelial growth factor (VEGF) receptors 1-3 [8] and has shown efficacy in several cancers [9][10][11] as well as preclinical glioma models [12,13]. In the phase 2 Regorafenib in Relapsed Glioblastoma (REGOMA) trial for first recurrence of a glioblastoma, REG increased the median OS from 5.6 to 7.4 months compared to lomustine [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recently completed Phase I trial demonstrated safety and preliminary data for activity in locally advanced extremity STS [ 24 ]. Regorafenib is a second generation multi-kinase inhibitor with activity and mechanism of action similar to sorafenib [ 25 ]. Regorafenib is approved for the treatment of metastatic colon cancer and advanced gastrointestinal stromal tumors [ 26 ].…”
Section: Introductionmentioning
confidence: 99%